Relative Sea-Level Changes and their Impact on Coastal Zones (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In the last few centuries, the study of sea-level changes along the world's shores has been a primary scientific focus in analyses of climate change, but also for scientists exploring past landscape evolution, geomorphological processes, human impacts, and system responses. The relative variation in sea level derives as a result of global, regional, and local processes. All these processes are spatially and temporally variable and cause complex sea-level changes at both regional and local scales. A multidisciplinary approach addressed to palaeo sea-level reconstructions at regional and local scale is the best method to understand the role of natural and anthropogenic forcing in the landscape evolution, as well as to discover the historical human adaptions to natural modifications of the landscape. Definitely, investigating these regional and local patterns is mandatory to reconstruct possible scenarios of the relative sea level rise impacts and to prepare the adaptation of coastal communities threatened by future climate changes. The aim of this Special Issue has been to collect contributions addressing and discussing methodological and multi-disciplinary approaches to studying the regional and local coastal modifications in relation to historical and recent relative sea-level changes to hypothesize future trends.